PENERAPAN TOTAL QUALITY MANAGEMENT DALAM UPAYA PEMENUHAN STANDAR NASIONAL PENDIDIKAN DI MAN 2 KARANGANYAR - Lutfi Nur Fathimah (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
This study aims to describe the implementation of Total Quality Management (TQM) at MAN 2 Karanganyar and its relation to the National Education Standards (NES), as well as the obstacles encountered in maintaining the quality of education. The research employed a descriptive qualitative method. Data were collected through interviews with an educational staff member at MAN 2 Karanganyar. The findings reveal that the implementation of TQM has been carried out comprehensively by involving all school elements to support the achievement of the eight National Education Standards. This is realized through systematically designed and revised curricula, teacher training and certification, regular supervision by school leaders, the development of facilities and infrastructure, transparent financial management, and the provision of student skills in religious fields as well as work-related competencies such as culinary arts, fashion design, and graphic design. The study also identifies challenges in the form of resistance to change and an organizational culture that has not fully supported continuous improvement. To address these challenges, consistent leadership, intensive socialization, ongoing training, and the development of a participatory quality culture are required.